Welty honored, campus celebrates African People's History Month - Uribes, Tom::::::::: (2013)
Fresno State President John D. Welty was honored Saturday for his nearly 22 years of service at the Black History Month 'Trailblazers Banquet' at the African American Historical and Cultural Museum of the San Joaquin Valley.